STRUCTURE OF THE FUNDAMENTAL SOLUTION OF CAUCHY PROBLEM FOR KOLMOGOROV SYSTEMS OF SECOND-ORDER - Малицька, Ганна Петрівна; Буртняк, Іван Володимирович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
We study the structure of the fundamental solution of the Cauchy problem for a class of ultra parabolic equations with a finite number of groups of variables which degenerates parabolic.